REVITALISASI PENDIDIKAN KEWARGANEGARAAN BAGI GENERASI MILENIAL - Humaidi, Humaidi (STAI AL FALAH Banjarbaru, 2019)
Citizenship Education is a subject that focuses on the formation of citizens who understand and are able to exercise their rights and obligations to become intelligent, skilled Indonesian citizens, characterized by the Pancasila and the 1945 Constitution of the Republic of Indonesia. Citizenship education is broadly formulated to include a process of preparing young people to take on their roles and responsibilities as citizens, and in particular, the role of education including schooling, teaching, and learning, in the process of preparing citizens. Millennials as part of the Indonesian nation's children are expected to understand citizenship education and become citizens who have a strong and consistent commitment to defend the Republic of Indonesia (NKRI). Kaerna The essence of the unitary state of the Republic of Indonesia is a modern nation-state. The modern nation-state is the state whose formation is based on the spirit of nationality or nationalism, namely on the determination of society to build a common future under the same country, even though the people of that community differ in their religion, race, ethnicity or class. Keywords: Revitalization, PKn, and the millennial generation.